Peran Orangtua dalam Pendidikan Seksual Anak Usia Dini pada Keluarga Muslim di Kampung Pinang Sebatang Kecamatan Tualang Kabupaten Siak - Ahmad Badarudin; Eva Dewi; Tohirin (Jurnal Dirosah Islamiyah, 2025)
Sexual education for children is less noticed by parents so they do not provide an understanding about it even though children have been taught sexual education since early age. Children at an early age say dirty words such as saying genitals when fighting and joking with their friends, boys imitate the style of girls and vice versa, excessive joking such as carrying and holding each other's bodies, peeking at the opposite sex when in the bathroom. Sexual education is the provision of information and the formation of attitudes and beliefs about sex, sexual identity, relationships, and intimacy. This concerns human sexual anatomy, reproduction, sexual relations, reproductive health, emotional relationships and other aspects. Not only explaining about sexual relations between husband and wife. This research was conducted in Sekarmayang Hamlet, Pinang Sebatang Village, Tualang District, Siak Regency. With a qualitative descriptive research approach, it explains the phenomena that occur related to early childhood sexual education. Parents have a role in their children's sexual education. The role of parents in sexual education is the role of parents as educators, the role of parents as role models, the role of parents as caregivers and caregivers, the role of parents as facilitators and the role of parents as mitators. In carrying out these roles, parents have supporting factors and inhibiting factors in the implementation of sexual education. Supporting factors in children's sexual education such as economy, good knowledge, good environment and good friends for children. Inhibiting factors in sexual education for children such as parental work, lack of sexual education knowledge, poor environment and poor friends.